Pelatihan Melukis dan Membatik Menggunakan Indikator Alami untuk Siswa MTsN 3 Aceh Timur - Juwairiah Juwairiah; Yurda Fitri; Khairiah; Muhammad Reza; Kaisya Rahmianza Syahputri; Fahada Husna; Nana Mauliza; Alfi Raihani; Refi Marisca; Putri Balqis; Afni Zalfa Zahira; Zahara Monalisa (LSM Catimore dan Sahabat, 2026)
The training on painting and batik-making through a chemical approach was a community service activity that utilized natural acid-base indicators as organic dyes. This program was conducted at MTsN 3 East Aceh and involved 24 ninth-grade students. The objectives of the training were to enhance students' knowledge, skills, and creativity in painting and batik-making using chemistry principles. The implementation methods consisted of material presentations, demonstrations, hands-on practice, and evaluation. Based on the evaluation results, 70.83% of participants gained a good understanding of the material, while 8.33% achieved an excellent level of comprehension. The assessment of the students' work indicated that the majority were able to produce creative and neat pieces while correctly applying the natural indicators. Furthermore, student enthusiasm remained high throughout the activity. These results demonstrated that the chemistry-based painting and batik-making training was effective in improving students' understanding, creativity, and learning motivation through a fun and applicable practical approach